PERAN MEDIA PEMBELAJARAN INTERAKTIF DALAM MENINGKATKAN MOTIVASI DAN HASIL BELAJAR BAHASA INDONESIA SISWA KELAS 5 SEKOLAH DASAR - Bella Tondang; Heliza Ayuningsi Sitorus; Imel Fitaloca Tambunan; Meyliana Perwita Saragih; Naswa Amirah (ADIBA : JOURNAL OF EDUCATION, 2024)
This research was motivated by the students' lack of understanding of Indonesian language learning activities. This research targets students who are still in grade 5 of elementary school, especially students who are disinterested in learning Indonesian due to the lack of variety in learning media. This research is directed at examining the role of more innovative and creative learning media in supporting Indonesian language skills in grade 5 elementary school. The research method used in this research is a literature review, namely a study that analyzes various sources such as related literature such as journals, books and scientific articles. The results of the literature review show that innovative learning media, such as digital-based educational games, interactive learning videos, mobile learning applications and various other learning media that use technology creatively and innovatively are adapted to current developments and also the needs of students. By increasing the penetration of students' learning motivation and strengthening their understanding of Indonesian language material. Apart from that, the use of innovative learning media is also aimed at creating a pleasant learning climate and environment and supporting the understanding of 5th grade elementary school students.